Determination of bulk domain structure and magnetization processes in bcc ferromagnetic alloys: Analysis of magnetostriction in Fe83Ga17 - Coey, John; He, Yangkun; Schaefer, Rudolf; Jiang, Chengbao (My University, 2018)
The ground state of macroscopic samples of magnetically ordered materials is a domain state because of magnetostatic energy or entropy, yet we have limited experimental means for imaging the bulk domain structure and the magnetization process directly. The common methods available reveal the domains at the surface or in electron- or x-ray transparent lamellae, not those in the bulk. The magnetization curve just reflects the vector sum of the moments of all the domains in the sample, but magnetostriction curves are more informative. They are strongly influenced by the domain structure in the unmagnetized state and its evolution during the magnetization process in an applied field. Here we report a method of determining the bulk domain structure in a cubic magnetostrictive material by combining magneto-optic Kerr microscopy with magnetostriction and magnetization measurements on single crystals as a function of applied field. We analyze the magnetostriction of Fe83Ga17 crystals in terms of a domain structure that is greatly influenced by sample shape and heat treatment. Saturation magnetostriction measurements are used to determine the fraction of domains orientated along the three ⟨100⟩ axes in the initial state. Domain wall motion and rotation process have characteristic signatures in the magnetostriction curves, including those associated with the ΔE effect and domain rotation through a ⟨110⟩ auxetic direction.
PUBLISHED
Keywords: Domains; Ferromagnetism; Magnetostriction; FABRICATION; NANOSTRUCTURES; Physics